PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING BERBANTUAN GEOGEBRA UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Nurhayati, Nurhayati; Zuhra, Fatma; Salehha, Osey Putri (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2021)
This research is based on teachers who rarely use learning models and media to support the learning process so that students are not interested in learning. This study aims to know whether differences in student learning outcomes taught using the Geogebra-assisted Project Based Learning (PjBL) learning model and those taught using conventional learning at SMAN 2 Bireuen. This research is a quasi-experimental research with a quantitative approach. The design used is the Pretest Posttest Control Group Design. The population in this research is all students of class X SMAN 2 Bireuen. In this research, we use the purposive sampling technique. The instrument used is a test consisting of pretest and post-test. N-gain was used to find out the increase in students' pretest and post-test scores. The results of the N-gain calculation show that the application of the Geogebra-assisted PjBL learning model can improve student learning outcomes